Development, characterization and pharmacokinetic evaluation of raloxifene-loaded transfersomes and ethosomes for transdermal delivery - Syed Mahmood (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Raloxifene HCl is a second generation selective estrogen receptor modulator (SERM), used primarily in osteoporosis and also finds a potential use in invasive breast cancer. This drug has a poor bioavailability, which is limited to only 2%. This study aims to develop lipid nanocarriers, transfersome and ethosomes for transdermal delivery of raloxifene HCl to improve its bioavailability. A total of twenty transfersomal formulations divided into four groups, each group containing different surfactants like Span-80, Span-85, sodium deoxycholate and a mixture of Span 80 + Span 85 (50:50) at various lipid and surfactant ratios were prepared by a rotary evaporation method. Five ethosomal formulations using different ethanol percentages ranging from 20 to 40% v/v were prepared while keeping the amounts of lipid and drug constant for each of the formulations. Particle sizes and their distribution, zeta-potential, entrapment efficiency (EE%) and transdermal flux were measured for all the formulations. The optimised formulations, both for transfersomes and ethosomes, were selected based on the highest EE% and transdermal flux. Four transfersomes (TS-80-5, TS-85-5, TS-(80+85-5) & TSD-4) with sizes of 110.7± 0.23, 115.5± 0.37, 101.4± 0.25, 92.37± 1.85 nm respectively and one ethosome (ER-1) with size of 150.73±4.10 nm were selected for further studies. The maximum EE% and flux (J) were found to be 92.00 ±0.28%, 8.39±0.69 µg/cm2hr and 62.65±0.63% and 22.14±0.83 µg/cm2hr for transfersomal and ethosomal formulations, respectively. Force emission scanning microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) revealed a smooth spherical morphology with nanosized bilayer vesicular structures. Atomic force microscopy (AFM) showed a clear topological view of the vesicles with a uniform size distribution. Confocal scanning laser microscopy (CLSM) clearly showed the vesicles' depth of permeation into the epidermis and dermis layers. Differential scanning calorimetry (DSC) confirmed the fluidity in the vesicle's membrane due to the presence of different surfactants within the vesicles. Attenuated total reflectance (ATR) and DSC studies further confirmed the fluidic nature of lipid vesicles on differently treated animal skins. XRD study showed the amorphous state of raloxifene in the formulations selected. 31P-NMR demonstrated Lorentzian lineshapes which indicate that the particles sizes are small. Cytotoxicity study was carried out on all the optimised formulations together with the liposomes, drug and its hydroalcoholic solution while using only PC-90G as a control. A decrease in cell viability was observed as the concentration of the all the optimised formulation increased. Three months physical stability studies performed on the optimised vesicular formulations indicated that they remain stable when stored at 4°C. The pharmacokinetic studies in the rat model were performed after converting the optimised formulations into a gel. The highest AUC0-48 recorded for TSD-4 was 7039.87 ng hr/ml with a half-life of 8.8 hrs, for ethosomes they were 4473.73 ng hr/ml and 8 hrs and for oral suspension they were 2841.18 ng hr/ml and 5.33 hrs, respectively. As compared to oral suspension, the best formulations of transfersomes and ethosomes increased the bioavailability of raloxifene HCl 247% times and 157% times, respectively and they were also superior to conventional liposome and hydroalcoholic drug solution in that respect. In conclusion, these nano-lipid formulations in form of transfersomes and ethosomes have shown a high potential as carriers for transdermal delivery of raloxifene HCl.